The living wage in the UK – an analysis of the GMB campaign in local government. (2nd January 2016) - Prowse, Peter; Fells, Ray
ABSTRACT: The adoption of a statutory national minimum wage policy in the UK is proving ineffective in resolving the problem of low pay. The emergence of living wage campaigns in the UK follows similar developments in the USA, and more recently, New Zealand. Rather than focus on a particular employer-specific campaign, this paper explores the campaign of the General and Municipal Boilermakers Union (GMB) in local government which recruits members from low-paid occupations. The 11 local government sector cases examine contracted workers allied to local government services, drawing on interviews with full-time officers, lay representatives and members involved in the campaigns. Nine campaigns were successful and two were not. The Union's strategy revealed an interplay between industrial and political influences and, despite the social-economic nature of the issue, the limited extent of involvement of social movements in the campaign.